INOVASI PEMBERDAYAAN MASJID DALAM PENGEMBANGAN PENDIDIKAN ISLAM DI SINGAPURA - Dja’far Siddik (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2010)
Abstract: Innovasion in Empowering Mosque for the Development of Islamic Education in Singapore. In contrast to the most generally accepted function of mosque for ritual observance, Singapore has stepped forward intransforming the role of mosque as an institution of Islamic education. Under the management of Islamic Religious Counsil of Singapore, in the year 2000 Singapore Islamic Education System (SIES) drafted new program for mosque education which was then taken into effect four years later. The author maintains that the introduction of this program not only cater the need of Muslims at all level of age but also provide room for the non-Muslim or what is the so called harmony centre. Based on field research in Singapore, this sutdy then focuses on analyzing what kind of distinct features that the program brought with it in empowering the roleof mosque for the development of Islamic education in the region. To be precise, the paper discusses the reforms made to mosque education which constitute considering the program, content, targetted audience and facilities. Kata Kunci: masjid, pendidikan Islam, Majelis Ugama IslamSingapura, MENDAKI, dan Sesi Program a LIVE